(untitled) (Agroindustrial Science, 2022)
In the present work, the effect of temperature on the rheological properties of the industrialized honey of three different high-trade brands in the northern, central and southern Lima markets was studied. The physicochemical characteristics of water activity, specific gravity, moisture content, brix degrees, refractive index and pH were analyzed. No significant difference was found between the values ​​of the physicochemical properties within and between the groups of the commercial brands analyzed (p> 0.05). The industrialized honey was tested with a Brookfield RVDV-E concentric viscometer using a flat disk spindle at five temperature levels from 20 ºC to 60 ºC, and the influence of temperature with dynamic or absolute viscosity was studied. Through the rheogram, a behavior of a Newtonian fluid was observed. For all samples it was found that the mean absolute viscosity decreases with temperature at 20 ºC (7430 mPa∙s), 30 ºC (2636 mPa∙s), 40 ºC (955 mPa∙s), 50 ºC (440 mPa∙s) and 60 ºC (267 mPa∙s). The dependence of the viscosity with the temperature was described by a mathematical exponential model of three constants proposed in this investigation that gave a good fit, obtaining a coefficient of determination of 0.9999. The activation energy value calculated and within the temperature range tested was 68.73±0.129 kJ.mol-1. The results obtained in this study are of great interest to the industry that manipulates and formulates edible foods based on this type of product.